2019
DOI: 10.3390/ani9080525
|View full text |Cite
|
Sign up to set email alerts
|

Hermetia illucens Larvae Reared on Different Substrates in Broiler Quail Diets: Effect on Physicochemical and Sensory Quality of the Quail Meat

Abstract: This research aimed at improving the fatty acid (FA) profile of Hermetia illucens larvae (HI) and evaluating the effects of their inclusion in growing broiler quails’ diets on the meat physicochemical quality, including detailed amino acid (AA) and FA profiles, sensory traits, and retail display. HI larvae were reared on two different substrates: layer mash (HI1) and 50:50 layer mash/fish offal (HI2). A total of 300 10-day-old quails were allocated to the three dietary groups (five replicates/each): a soybean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 50 publications
4
22
1
Order By: Relevance
“…Nonetheless, the pH values observed from these studies were normal for poultry meat. The lack of dietary effects on color is consistent with the findings of Secci et al [29] and Cullere et al [30]; however, it was expected that the presence of carotenoids (~2.15 mg/kg) in BSFL meal would improve the yellowness of the meat [29]. In this study, no dietary effects were observed on drip loss, WHC, and shear force.…”
Section: Discussionsupporting
confidence: 91%
“…Nonetheless, the pH values observed from these studies were normal for poultry meat. The lack of dietary effects on color is consistent with the findings of Secci et al [29] and Cullere et al [30]; however, it was expected that the presence of carotenoids (~2.15 mg/kg) in BSFL meal would improve the yellowness of the meat [29]. In this study, no dietary effects were observed on drip loss, WHC, and shear force.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have investigated the effect of dietary treatment on chicken meat quality [20,[38][39][40]. Results indicated that the volatile profile was affected by dietary treatments, with the majority of the compounds having been reported in literature on chicken meat aroma ( Supplementary Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…Shaping insect nutrient profile -The low level of some nutrients in insects could represent a limit in animal nutrition; however, it has been shown that the nutrient composition of insects is highly dependent on the rearing substrates Danieli et al 2019). For example, using substrates naturally containing polyunsaturated fatty acids (PUFA) or rich in minerals allow to obtain enriched insect-derived materials that are more suitable for feed purposes (Liland et al 2017;Cullere et al 2019;Koutsos et al 2019;Pinotti et al 2019). Thus, the insect nutrient profile can be modulated by appropriate dietary strategies, according to specific animal dietary requirements.…”
Section: Strengthsmentioning
confidence: 99%